Collaborative Secured Data Management System Using Blockchain - Ramamoorthy, S.; Rohila, Vishal; Sharma, Kshitiz (International Journal of Psychosocial Rehabilitation, 2020)
The proposed system uses blockchain technology to provide data integrity to the user of the network. Blockchain enables security in which data integrity can be checked without revealing the information of the user or the actual data. The proposed architecture consists of a Data Owner, Data Auditor and users. The user is the person whose data is in the system, Owner is the person who owns the database and auditors are the technicians who check the data if any data is compromised and make sure the data integrity is intact. The entire data is in the form of blocks and the technology of ring signatures will be used to provide authentication. This will provide a way to check the data without unveiling the original under signer of the data block. Also the information of the members present in the ring signatures group are kept confidential. This provides total security both to the data and user of the database.